First synthesis of human gastrin-II and radiolabeled cholecystokinin-octapeptides - Zarándi Márta; Penke Botond; Zsigo J.; Varga J.; Toth G.; Pelczer I.; Rivier J.; Kovacs K.; Tóth Gábor; Peptides 1984 Djurönäset 1984.06.10-1984.06.15 (Almqvist & Wiksell International Stockholm, 1984)
Human gastrin I pyroGlu-Gly-Pro-Trp-Leu-(Glu)5-Ala-Tyr(R)-Gly-Trp-Met-Asp-Phe-NH2 (I; R = H) (II) was prepd. by the solid-phase method on an α-methylbenzylhydrylamine resin and then it was o-sulfated with pyridine-SO3 or pyridinium acetylsulfate (PAS) in pyridine-DMF to give human gastrin II (I, R = SO3H) (III). II and III were also prepd. by classical soln. methods using minimal side-chain protection; the presence of 5 free γ-carboxyl groups in sequence 6-11 caused problems in azide formation and decreased the yield. The solid-phase synthesis of cholecystokinin octapeptide (CCK-8), H-Asp-X-Met-Gly-Trp-Met-Asp-Phe-NH2 [IV, X = Tyr(SO3H)], and caerulein was optimized using Trp(CHO) and Met(O) for protection and PAS for O-sulfation. Tritiated CCK-8 desulfate [IV, X = Tyr(3,5-3H)] was prepd. from IV [X = Tyr(3,5-I2)] (V) by an exchange reaction with 3H2/PdO; V was prepd. by the solid-phase method on a benzhydrylamine resin. Due to steric hindrance, the synthesis of tritiated CCK-8 failed; therefore, Nα-Fmoc-CCK-8 desulfate (Fmoc = 9-fluorenylmethoxycarbonyl) was prepd. by the solid-phase method and then it was O-sulfated with 35S-PAS and Fmoc-deblocked by Tesser's base to give 35S-labeled CCK-8. [on SciFinder(R)]
Keywords: Kémiai tudományok; Általános orvostudomány